(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Cholinergic receptors (acetylcholine receptors) are transmembrane receptors whose endogenous agonist ligand is acetylcholine. Acetylcholine is present in both pre- and postganglionic synapses of the parasympathetic system, as well as in preganglionic sympathetic synapses, a number of postganglionic sympathetic synapses, neuromuscular synapses (somatic nervous system), and also serves as a neurotransmitter in some parts of the central nervous system. Nerve fibers that secrete acetylcholine from their ends are called cholinergic fibers. This article provides information on drugs for the cholinergic system.